Long-term persistence of IgE anti-influenza A HIN1 virus antibodies in serum of children and adults following influenza A vaccination with subsequent H1N1 infection: a case study - Smith-Norowitz TA; Kusonruksa M; Wong D; Norowitz MM; Joks R; Durkin HG; Bluth MH (Dove Medical Press, 2012)
Tamar A Smith-Norowitz,1 Melanie Kusonruksa,2 Darrin Wong,2 Moshe M Norowitz,2 Rauno Joks,3 Helen G Durkin,2 Martin H Bluth41Department of Pediatrics, 2Department of Pathology, 3Department of Medicine, Center for Allergy and Asthma Research, SUNY Downstate Medical Center, Brooklyn, New York, NY; 4Department of Pathology, Wayne State University School of Medicine, Detroit, MI, USABackground and methods: The role of immunoglobulin (Ig) E in immunity against influenza A H1N1 has not been studied. Total serum IgE and specific IgE and IgG anti-H1N1 virus responses were studied in children and adults (n = 2) who received influenza virus vaccination (Flumist® or Fluzone® ) in autumn 2008 and 2009, and then subsequently became infected with the H1N1 virus in spring 2009. Twelve months after infection, antibodies in their serum were compared with those in the serum of subjects who were either vaccinated but not infected (n = 4) or nonvaccinated and noninfected subjects (n = 2), using UniCAP total IgE fluoroenzyme immunoassay, sodium dodecyl sulfate polyacrylamide gel electrophoresis, and Western blotting. Band sizes for the influenza virus (58, 56, 40, 30, 25, and 17 kDa) and H1N1 viral proteins (58, 56, 25, and 17 kDa) were determined, using sodium dodecyl sulfate polyacrylamide gel electrophoresis and Coomassie brilliant blue.Results: We found that the serum of vaccinated and subsequently infected children and adults contained IgE and IgG antibodies to both H1N1 and influenza virus, with a strong IgE and IgG band intensity at 56 kDa. Interestingly, in subjects who were vaccinated but not infected, band intensity at 56 kDa was lowered by approximately two-fold. Serum of nonvaccinated and noninfected subjects had no detectable IgE or IgG antibodies to influenza virus or H1N1.Conclusion: This is the first description of IgE anti-influenza A H1N1 antibodies in human serum and the first demonstration of their long-term persistence. The decreased intensity of the 56 kDa band in vaccinated noninfected subjects compared with vaccinated infected subjects suggests augmented IgE and IgG antibody responses to influenza A H1N1.Keywords: influenza A H1N1, immunoglobulin E, vaccination